Whole exome sequencing reveals novel LEPR frameshift mutation in severely obese children from Western India. Issue 7 (8th May 2019) - Bhatt, Arpan; Purani, Charul; Bhargava, Poonam; Patel, Komal; Agarbattiwala, Tanvi; Puvar, Apurvasinh; Shah, Krati; Joshi, Chaitanya G.; Dhamecha, Nidhi; Prabhakar, Mukund; Joshi, Madhvi
Abstract: Background: Obesity, especially early onset of obesity is a serious health concern in both developed and developing countries. This is further associated with serious comorbidities like a fatty liver disease, cardiovascular diseases, type‐2 diabetes, obstructive sleep apnea, renal complications and respiratory problems. Many times early onset of obesity is linked with heritable monogenic, polygenic and syndromic forms. Globally, studies on roles of genes involved in early onset of obesity are limited. Methods: Here in this study, a consanguineous family of Western Indian origin having four siblings, one unaffected and three affected with severe early onset of obesity was enrolled. Affected siblings also displayed comorbidities like mild to moderate obstructive sleep apnea, raised Renal Resistance Index, oliguria, and severe anemia. Whole Exome Sequencing (WES) of Trio with one affected and unaffected sibling was done. Data analysis was performed to check pathogenic mutation segregation in unaffected parents with affected and unaffected sibling. Results: WES of trio identified novel frameshift mutation in the LEPR gene resulting in truncated leptin receptor (LEPR). The same mutation was confirmed in other affected siblings and two siblings of distant relatives by Sanger sequencing. The possible effects of truncating mutation in LEPR function by in silico analysis were also studied. Conclusion: Understanding genetic basis of obesity might provide a clue for better management and treatment in times to come. This work demonstrates identification of novel mutation in LEPR gene resulting into early onset of obesity. Discovery of novel, population‐specific genomics markers will help population screening programs in creating base for possible therapeutic applications and prevention of this disease for next generations. Abstract : This work demonstrates a use of whole exome sequencing of Trio for some severe morbid conditions that can lead to the discovery of novel mutation.